Subsurface Microbial Habitats in an Extreme Desert Mars-Analog Environment - Warren-Rhodes, Kimberley A.; Lee, Kevin C.; Archer, Stephen D. J.; Cabrol, Nathalie; Ng-Boyle, Linda; Wettergreen, David; Zacny, Kris; Pointing, Stephen B.; , The NASA Life in the Atacama Project Team (Frontiers in Microbiology, 2019)
Sediments in the hyper-arid core of the Atacama Desert are a terrestrial analogue to Mars regolith. Understanding the distribution and drivers of microbial life in the sediment may give critical clues on how to search for biosignatures on Mars. Here, we identify the spatial distribution of highly specialised bacterial communities in previously unexplored depth horizons of subsurface sediments to a depth of 800mm. We deployed an autonomous rover in a mission-relevant Martian drilling scenario with manual sample validation. Subsurface communities were delineated by depth related to sediment moisture. Geochemical analysis indicated soluble salts and minerology that influenced water bio-availability, particularly in deeper sediments. Colonization was also patchy and uncolonized sediment was associated with indicators of extreme osmotic challenge. The study identifies linkage between biocomplexity, moisture and geochemistry in Mars-like sediments at the limit of habitability and demonstrates feasibility of the rover-mounted drill for future Mars sample recovery.